Microglia/macrophages express alternative proangiogenic factors depending on granulocyte content in human glioblastoma. Issue 2 (24th November 2020) - Blank, Anne; Kremenetskaia, Irina; Urbantat, Ruth M; Acker, Güliz; Turkowski, Kati; Radke, Josefine; Schneider, Ulf C; Vajkoczy, Peter; Brandenburg, Susan
Abstract: Myeloid cells are an inherent part of the microenvironment of glioblastoma multiforme (GBM). There is growing evidence for their participation in mechanisms of tumor escape, especially in the development of resistance following initially promising anti‐VEGF/VEGFR treatment. Thus, we sought to define the capability of myeloid cells to contribute to the expression of proangiogenic molecules in human GBM. We investigated GBM specimens in comparison with anaplastic astrocytoma (WHO grade III) and epilepsy patient samples freshly obtained from surgery. Flow cytometric analyses revealed two distinct CD11b + CD45 + cell populations in GBM tissues, which were identified as microglia/macrophages and granulocytes. Due to varied granulocyte influx, GBM samples were subdivided into groups with low (GBM‐ l PMNL) and high (GBM‐ h PMNL) numbers of granulocytes (polymorphonuclear leukocytes; PMNL), which were related to activation of the microglia/macrophage population. Microglia/macrophages of the GBM‐ l PMNL group were similar to those of astrocytoma specimens, but those of GBM‐ h PMNL tissues revealed an altered phenotype by expressing high levels of CD163, TIE2, HIF1α, VEGF, CXCL2 and CD13. Although microglia/macrophages represented the main source of alternative proangiogenic factors, additionally granulocytes participated by production of IL8 and CD13. Moreover, microglia/macrophages of the GBM‐ h PMNL specimens were highly associated with tumor blood vessels, accompanied by remodeling of the vascular structure. Our data emphasize that tumor‐infiltrating myeloid cells might play a crucial role for limited efficacy of anti‐angiogenic therapy bypassing VEGF‐mediated pathways through expression of alternative proangiogenic factors. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.